ANALISIS PERFORMANSI SISTEM TRANSMISI DATA PADA KOMUNIKASI FREE SPACE OPTIC TERHADAP PEGARUH VARIASI JARAK - Adistya Fajar Qolby; Sholeh Hadi Pramono; Sapriesty Nainy Sari (Jurnal Mahasiswa TEUB, 2019)
Free Space Optic (FSO) is a communication system that uses a light source in the form of an LED or LASER (light amplification by stimulated emission of radiation) and passes it to the receiver using atmospheric propagation media. In this study experimental research was conducted, namely testing and analyzing the effect of distance variations on the performance of data transmission systems in free space optical communication. For variations the distance starts from 5 cm between the location of the laser on the transmitter to the location of the photodioda on the receiver while the maximum distance is set at 50 cm. Input data used experiment experiment data transmission process in the form of word data, images, animation, and audio. Data transmission system performance is reviewed in Loss, BER, and delaytime parameters. Loss value is proportional to increasing distance variation. The greater the distance the greater the loss value. Optical loss values ​​for all types of data have started to rise when the distance is 10 cm with a 5.88 dB and receiver loss transmitter 1.1491 dB and then reach a maximum of 50 cm when the optical loss at the transmitter is 6.305 dB and the receiver is 1.3219 dB. BER values ​​obtained in each type of data tend to be constant with varying distance variations. For input data type "word" BER value is 0. Input data type "image" BER value is 0.0071. Input type of "animation" BER value is 0.0075. Input of "audio" data type BER value is 0.0083. The biggest BER occurs in the audio data type because the bits transmitted are larger so there are many bit errors. The value of the delay is directly proportional to the distance variation. The greater the distance, the greater the value of delay. The delay time value for all types of data has started to rise when the distance of 10 cm with the lowest delaytime value of the word data type of 10.13 μs and then reaches a maximum of 50 cm with the audio data type of 27.09 μs. Index Terms— Free Space Optic, Transmiter, Receiver,  Loss, BER, delaytime.Abstrak – Free Space Optic (FSO) adalah sistem komunikasi yang menggunakan sumber cahaya berupa LED atau LASER (light amplification by stimulated emission of radiation) dan meneruskannya ke penerima menggunakan media propagasi atmosfer.  Pada penelitian ini dilakukan penelitian yang bersifat eksperimen yaitu menguji dan menganalisis pengaruh variasi jarak terhadap performansi sistem  transmisi data pada komunikasi free space optic. Untuk variasi jarak dimulai dari 5 cm antara dari letak laser pada bagian transmitter terhadap letak photodioda pada bagian receiver sedangkan jarak maksimum ditetapkan sebesar 50 cm. Data Input yang digunakan eksperimen proses trasmisi data berupa jenis data kata, gambar, animasi, dan audio. Performansi sistem transmisi data ditinjau pada parameter Loss, BER, dan delaytime. Nilai loss sebanding terhadap bertambahnya variasi jarak. Semakin besar jarak semakin besar pula nilai loss. Nilai optik loss untuk semua jenis data sudah mulai naik ketika jarak 10 cm dengan loss transmitter 5,88 dB dan receiver 1,1491 dB lalu mencapai maksimum pada jarak 50 cm ketika optik loss pada transmitter sebesar 6,305 dB dan receiver sebesar 1,3219 dB. Nilai BER yang didapatkan pada setiap jenis data cenderung konstan dengan variasi jarak yang berbeda-beda. Untuk input jenis data “kata” nilai BER sebesar 0. Input jenis data “gambar” nilai BER sebesar 0,0071. Input jenis data “animasi”  nilai BER sebesar 0,0075. Input jenis data “audio”  nilai BER sebesar 0,0083. BER paling besar terjadi pada jenis data audio dikarenakan bit yang ditransmisikan lebih besar sehingga terjadi banyak error bit. Nilai delaytime berbanding lurus dengan variasi jarak. Semakin besar jarak maka semakin besar nilai delaytime. Nilai delaytime untuk semua jenis data sudah mulai naik ketika jarak 10 cm dengan nilai delaytime terendah pada jenis data kata sebesar 10,13 μs lalu mencapai maksimum pada jarak 50 cm dengan jenis data audio sebesar 27,09 μs.Kata Kunci— Free Space Optic, Transmiter, Receiver,  Loss, BER, delaytime.